The association between empirical dietary inflammatory pattern and risk of cancer and cancer-specific mortality: a systematic review and meta-analysis of prospective cohort studies - Hosseini, Fatemeh S.; Nikparast, Ali; Etesami, Elahe; Javaheri-Tafti, Fatemeh; Asghari, Golaleh (Frontiers in Nutrition, 2024)
Background/Aim: Current evidence indicates a correlation between the inflammatory potential of diet and the risk of cancer and cancer-specific mortality. This study aimed to assess the association between empirical dietary inflammatory pattern (EDIP), which has recently been designed based on the inflammatory potential of the diet, and the risk of cancer and cancer-specific mortality. Methods: A literature search was conducted in PubMed/Medline, Scopus, and the Web of Sciences databases from their inception from January 2016 to March 2024. A random effects model was employed to calculate pooled Effect size (ES) and 95% confidence intervals (95% CI). The Cochran Q test and the I2 statistic were utilized to assess heterogeneity between studies. Results: From the initial 229 records, 24 prospective cohort studies with 2,683,350 participants and 37091 cancer incidence cases, as well as 20819 cancer-specific mortality, were included in our study. Pooled results demonstrated a significant association between higher adherence to EDIP and the risk of total cancer (ES:1.10;95%CI:1.05-1.15; I2=41.1), colorectal cancer (ES:1.19;95%CI:1.11-1.27; I2=41.1), and liver cancer (ES:1.48;95%CI:1.14-1.94; I2=36.9). However, no significant association between increased adherence to EDIP and the risk of ovarian or endometrial cancer was found. As well, greater adherence to EDIP was significantly associated with the risk of cancer-specific mortality (ES:1.18;95%CI:1.05-1.33; I2=45.4). Conclusion: Our results showed that a diet with higher inflammatory properties is associated with increased risk of cancer and cancer-specific mortality.